Response to the comment on “Primary open versus closed implantation strategy for totally implantable venous access ports: the multicenter randomized controlled PORTAS-3 trial (DRKS 00004900)” - Hüttner, Felix; Büchler, Markus W.; Diener, Markus K.; Knebel, Phillip (Annals of surgery, 2021)
An abstract is unavailable.